2009
DOI: 10.1345/aph.1k612
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Involvement in Improving Asthma Outcomes in Various Healthcare Settings: 1997 to Present

Abstract: Future study designs may require larger sample size and measure outcomes that better assess disease severity in asthma, such as impairment and risk domains. This review supports the National Heart, Lung, and Blood Institutes of the National Institutes of Health Expert Panel Report 3 guidelines in recognizing pharmacists as accessible healthcare practitioners who, via patient education and medication management, may help patients with asthma attain better control of their disease state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 40 publications
2
58
1
Order By: Relevance
“…Given the large body of evidence supporting the pharmacist's role in improving asthma outcomes in patients [37], the sustained increase in knowledge is not surprising. Our results suggest that pharmacy-based services are very efficient in terms of improvements and retention of asthma knowledge.…”
Section: "I Think When You've Been An Asthmatic a Long Time Previousmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the large body of evidence supporting the pharmacist's role in improving asthma outcomes in patients [37], the sustained increase in knowledge is not surprising. Our results suggest that pharmacy-based services are very efficient in terms of improvements and retention of asthma knowledge.…”
Section: "I Think When You've Been An Asthmatic a Long Time Previousmentioning
confidence: 99%
“…group education, individualized education and outreach education [34][35][36]. In most cases, asthma care programs have been delivered across a period of six months to a year, with very few reporting ongoing patient monitoring beyond the period of program delivery [37,38]. Moreover, many studies of pharmacy-based asthma care programs do not report on the 'frequency' of the education/care sessions [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] Services provided by pharmacists in community or ambulatory outpatient settings have been shown to improve medication management and adherence. 19,20 Whether pharmacist care is cost-effective remains to be determined.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…Systematic reviews summarizing the roles and/or impact of CP involvement in various specialty areas have been published. These areas include mental health, [16][17] diabetes, [18][19] nephrology, [20][21] heart failure, 22 asthma, 23 Alzheimer's disease, 24 and antibiotic management. 25 Knapp et al's (2005) 2004 survey of 233 ambulatory sites with CP involvement reported that the most common area of specialty CP involvement was oncology (28% of participating sites).…”
mentioning
confidence: 99%